1997
DOI: 10.1177/000331979704800113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Daflon 500 mg in Venous Leg Ulcer Healing: A Double-Blind, Randomized, Controlled Versus Placebo Trial in 107 Patients

Abstract: The objective of this study was to evaluate the efficacy of Daflon 500 mg (Dios)* in venous ulcers. A multicenter, double-blind, randomized, controlled versus placebo (Plac) trial was conducted, with stratification according to the size of ulcer (< or = 10 cm and > 10 cm). The protocol called for a two-month treatment with Dios (one tablet = 450 mg micronized purified Diosmin) or a placebo, two tablets/day, in addition to compression therapy. Evaluations were performed every fifteen days, from D0 to D60. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 11 publications
0
61
0
6
Order By: Relevance
“…Pentoxifylline, 43 aspirin, 44 diosmin, 45 among other drugs, are mentioned in the literature due to their apparent capacity to stimulate healing.…”
Section: Systemic Drugsmentioning
confidence: 99%
“…Pentoxifylline, 43 aspirin, 44 diosmin, 45 among other drugs, are mentioned in the literature due to their apparent capacity to stimulate healing.…”
Section: Systemic Drugsmentioning
confidence: 99%
“…According to these recommendations, study designs should be double-blind, placebo-controlled, randomized into parallel groups, with the following primary end-points: percentage of patients with complete ulcer healing and time for ulcers to achieve complete healing [27]. The study by Guilhou et al [24]evaluating the effect of MPFF in patients with venous ulceration, complies with all these recommendations except for the duration of treatment which was 2 months instead of 6 months. The study showed a significant increase in the number of ulcers that healed, and in the time required to achieve complete healing in ulcers that were ≤10 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…A double-blind, randomized, placebo-controlled multicenter trial with stratification according to ulcer size (≤10 and >10 cm) assessed the ability of MPFF to influence ulcer healing in addition to conventional compression therapy [24]. The treatment period was 2 months and the dosage 2 tablets of Daflon 500 mg per day for 107 patients presenting CVI and venous ulceration.…”
Section: Venous Ulcerationmentioning
confidence: 99%
“…Nel lavoro svolto da Ruckeley nel 1997 è riportata una spesa annua per il management delle ulcere venose nel nostro Paese di circa 243 miliardi di lire [32].…”
Section: Ulcere Venose Cronicheunclassified
“…il mesoglicano), gli idrossirutosidi (come l'oxerutina) [45,46], i farmaci costituiti da diosmina [32,47] e la pentossifillina [48].…”
Section: Terapia Sistemica Nell'ulcera Venosaunclassified